Women’s Empowerment in Livestock Index adopted by four International Development Research Centre projects to measure women’s empowerment in animal vaccine interventions - CGIAR Research Program on Livestock (2019)
The Women’s Empowerment in Livestock Index, created by ILRI and Emory University, was adopted by four projects under the Livestock Vaccine Innovation Fund of the International Development Research Centre, providing harmonized data to measure the empowerment of women as users, entrepreneurs and service providers in the livestock vaccine distribution/delivery chain. This is the first time the tool is being used by a major international funder at scale, reaching women participants across six countries (Kenya, Uganda, Rwanda, Senegal, Ghana, Nepal).